Prenatal development of oviduct in the Surti buffalo - BAISHYA, G; VYAS, K N (The Indian Journal of Animal Sciences, 2013)
Oviducts from clinically healthy Surti buffalo foetuses (55) were studied at 7 different phases of prenatal life, ranging from 41 to 305 days (2.8 to 102.5 cm CVR). The first evidence offormation of oviduct was observed in 41 days (2.8 cm CVR) embryos as an invagination of the coelorriic epithelium at the anterolateral aspect of the mesonephros - the open Mullerian groove. It became a tubular structure at 46 days (3.8 cm CVR) of gestation and was located within the mesonephric fold. The primary, secondary and tertifary oviductal mucosal folds appeared at 94 days (14.5 cm CVR), 158 days (37.5 cm CVR) and 191 days (52.0 cm CVR) foetuses, respectively. A circular condensation and differentiation of the mesenchyme around the duct was noticed in 50 days (4.8 cm CVR) embryos, which progressed with vancing gestational age. Mucosa, muscularis and serosa could be identified at 128 days (24.0 cm CVR) and resembled that of adult organ at 191 days (52.0 cm CVR) foetuses. The average number and height of primary mucosal folds and the thickness of oviductal tunics revealed an increasing trend with advancing foetal age.